BANTUAN USAID KEPADA INDONESIA DALAM MENANGANI KASUS AVIAN INFLUENZA (AI) DI INDONESIA PADA TAHUN 2006-2010 - Sayoga, Putu Adi; Sushanti, Sukma; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRACT The current concern for a pandemic arises from an unprecedented outbreak of H5N1 influenza in birds and has spread across bird populations in Asia, Europe, and Africa. Given the rapid speed of transmission and the universal susceptibility of human populations, an outbreak of pandemic influenza anywhere poses a risk to populations everywhere. Indonesia suffers major loss due to high prevalence of the virus across the nation. The government undertakes several significant steps to address the issue, yet the numbers of infections are climbing up. The United States Agency of International Development builds upon a series of recent actions such as foreign aid, to eliminate negative implications on global scale as part of international respond toward transnational diseases outbreak. Through CBAIC, the agency collaborates with health authorities in Indonesia to prevent the pandemic of H5N1 virus, builds the capacity of the Indonesian government for pandemic response and reduce the occurrence of AI in poultry and humans. Keywords: transnational disease, avian influenza, foreign aid, USAID